SUSTAINABLE SUPPLY CHAIN MANAGEMENT IN WATER RETICULATION WORKS - Shaiful Fahmi, Nurul Ain; Marhani, Mohd Arif; Raja Muhammad Rooshdi, Raja Rafidah; Ismail, Noor Akmal Adillah; Sahamir, Shaza Rina (Journal of Civil Engineering, Science and Technology, 2025)
Since the emergence of sustainability, people have generally focused on issues related to the triple bottom line: social, economic, and environmental. This paper focuses on the integration of sustainability and supply chain management in the construction industry, particularly in water reticulation works. The peculiarities in documentation and technical issues encountered during the water reticulation works had prompted the need for this research. The challenges associated with the implementation of sustainable supply chain management in water reticulation works in Malaysia were identified, and improvements were suggested to overcome these challenges. A qualitative study was conducted by having a case study on six different packages of pipe replacement projects. An in-depth interview was carried out with semi-structured questions based on predetermined themes identified in the literature review. Based on the findings from four participants who were interviewed, they corroborated the costs, management, technical capabilities, complexities, mindset, and cultural changes. In conclusion, industry professionals can expand on numerous management facets to enhance future improvements.